Coronavirus Disease-19: An Interim Evidence Synthesis of the World Association for Infectious Diseases and Immunological Disorders (Waidid) - Abu-Raya, Bahaa; Migliori, Giovanni Battista; O'Ryan, Miguel; Edwards, Kathryn; Torres, Antoni; Alffenaar, Jan-Willem; Märtson, Anne-Grete; Centis, Rosella; D'Ambrosio, Lia; Flanagan, Katie; Hung, Ivan; Lauretani, Fulvio; et al. (Frontiers in Medicine, 2020)
Abstract Coronavirus disease 2019 (COVID-19) is a rapidly evolving, highly transmissible and potentially lethal pandemic caused by a novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As of 11 June 2020, more than 7,000,000 COVID-19 cases have been reported worldwide, and more than 400,000 patients have died, affecting at least 188 countries. While literature on the disease is rapidly accumulating, an integrated, multinational perspective on clinical manifestations, immunological effects, diagnosis, prevention and treatment of COVID-19 can be of global benefit. We aimed to synthesize the most relevant literature and experiences in different parts of the world through our global consortium of experts to provide a consensus-based document at this early stage of the pandemic.